TURKEY : ECONOMIC ADVANTAGES OF JOINING THE EUROPEAN UNION (EU) - Shahrir Nazmi Md Salleh (Tesis, 2022)
This research will be dedicated to three objectives the first objective is to identify is to identify Turkey and EU relations. The second objective of this research will be to focus on analysing Turkey's economic challenges, sources and strengths. The last objective of this research is to analyse the effect of the advantages of Turkey's economy.